1978
DOI: 10.1007/bf00432853
|View full text |Cite
|
Sign up to set email alerts
|

The effects of scopolamine on extinction and spontaneous recovery

Abstract: The effects of scopolamine hydrobromide on baseline extinction levels and spontaneous recovery were assessed. Rats were trained on one of four reinforcement schedules (CRF, FR 10, FR 20, FR 40) with either food or water reinforcement. Scopolamine increased response rates in extinction and spontaneous recovery following training on all four schedules when the reinforcer was water, but had no effect on responding previously maintained by food. The results are discussed in terms of the limitations of a general th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Since scopolamine produces dry mouth and increased heart rate (Innes & Nickerson, 1975), central cholinergic effects can be concluded only after the demonstration that results from scopolamine do not occur after administration of quaternary ammonium analogues (e.g., methylscopolamine) that do not cross the blood brain barrier easily. Such evidence has been provided for scopolamine effects on resistance to extinction in water-motivated tasks (Morley & Russin, 1978). The present experiment includes a test for peripheral anticholinergic effects and demonstrates that scopolamineinduced increases in resistance to extinction of ICSS are mediated by the central nervous system.…”
supporting
confidence: 54%
See 2 more Smart Citations
“…Since scopolamine produces dry mouth and increased heart rate (Innes & Nickerson, 1975), central cholinergic effects can be concluded only after the demonstration that results from scopolamine do not occur after administration of quaternary ammonium analogues (e.g., methylscopolamine) that do not cross the blood brain barrier easily. Such evidence has been provided for scopolamine effects on resistance to extinction in water-motivated tasks (Morley & Russin, 1978). The present experiment includes a test for peripheral anticholinergic effects and demonstrates that scopolamineinduced increases in resistance to extinction of ICSS are mediated by the central nervous system.…”
supporting
confidence: 54%
“…the same effects as scopolamine hydrobromide, it can now be concluded that the mechanism is a central one. Increases in extinction responding in tasks involving natural rewards have been found after scopolamine administration in some (Hearst, 1959;Heise et aI., 1970;Herblin, 1968;McKim, 1970;Morley & Russin, 1978;Stone, 1964), but not all (McKim, 1980;Morley & Russin, 1978) experimental situations. Olds (1970) found that fast ICSS responders (>94 responses/min) showed a decrease in barpressing following scopolamine administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore not entirely inconceivable that the differing findings in extinction for the two experiments might also be attributable to the choice of reinforcement (food vs. water) and/or the associated instrumental act (lever press vs. licking). Macdonald and Toledo (1974) had observed a PREE using food but not water as reward, although subsequent studies reported that the PREE can occur regardless of whether the reinforcement was water or food (Mellgren, Hoffman, Nation, Williams, & Wrather, 1979; Morley & Russin, 1978; Seybert, Gerard, Lawrence, Nash, & Williams, 1976).…”
Section: Discussionmentioning
confidence: 99%